2016
DOI: 10.5762/kais.2016.17.12.71
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors and Sexual Experience of Adolescents in Korea

Abstract: Lee, GyuyoungRed Cross College of Nursing, Chung-Ang University. Abstract Purpose: The aim of this study was to identify sexual experiences and associated factors among middle and high school students in Korea. Methods: Data were analyzed from 74,186 participants who completed the 2012 Korea Youth Risk Behavior Web-based Survey. Descriptive statistics were used to identify the condition of sexual behavior, and a complex sample logistic regression was used to examine the factors related to sexual behavior. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…The nding was supported by a study conducted in Wollega, Ethiopia (19). It was also congruent with studies conducted in Mexico and Korea (4,7,(36)(37)(38). The possible reason for this association may be due to cultural malpractices like early marriage and abduction which were common but, decreased in the last ve years as the data represents at what age they started rst sex.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The nding was supported by a study conducted in Wollega, Ethiopia (19). It was also congruent with studies conducted in Mexico and Korea (4,7,(36)(37)(38). The possible reason for this association may be due to cultural malpractices like early marriage and abduction which were common but, decreased in the last ve years as the data represents at what age they started rst sex.…”
Section: Discussionsupporting
confidence: 85%
“…Different scholars de ne early sexual initiation according to the social and demographic context of the nation (7)(8)(9). But, the Universal Declaration of Human Rights proclaimed as age below 18 years old is considered as a child, they couldn't decide concerning marriage and/or consensual sexual relationship (10).…”
Section: Introductionmentioning
confidence: 99%
“…The results from our study using KYRBS are consistent with those of previous studies that showed that the prevalence of sexual experience at age 12 has generally increased in recent cohorts. Moreover, Lee [47] reported that 22.3% of adolescents had their first sexual experience in elementary school, 39.4% in middle school, and 38.2% in high school. This implies that the prevalence of sexual experience in Korean adolescents may continue to increase in the future.…”
Section: Discussionmentioning
confidence: 99%
“…There is no universal agreement on de nition of early sexual initiation. Different scholars de ne it according to the social and demographic context of the nation (7)(8)(9). But according to Universal Declaration of Human Rights, individuals below 18 years old are considered as child, who cannot make decision in relation to marriage and/or consensual sexual relationship.…”
Section: Introductionmentioning
confidence: 99%